2003
DOI: 10.1002/ijc.11490
|View full text |Cite
|
Sign up to set email alerts
|

Fruits, vegetables and lung cancer: A pooled analysis of cohort studies

Abstract: Inverse associations between fruit and vegetable consumption and lung cancer risk have been consistently reported. However, identifying the specific fruits and vegetables associated with lung cancer is difficult because the food groups and foods evaluated have varied across studies. We analyzed fruit and vegetable groups using standardized exposure and covariate definitions in 8 prospective studies. We combined study-specific relative risks (RRs) using a random effects model. In the pooled database, 3,206 inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
171
3
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(194 citation statements)
references
References 91 publications
14
171
3
4
Order By: Relevance
“…43 Intake of vegetables in Western countries is lower than in South Asian populations. The median intake of total vegetables, including pulses, among the controls in our study was 355 g/day, much higher than in the cohorts included in the pooled analysis (range: 77-226 g/day 32 ). Thus, the lower intake of vegetables and dietary fibre might have reduced the likelihood of finding associations in studies conducted among Western populations.…”
Section: Discussioncontrasting
confidence: 57%
“…43 Intake of vegetables in Western countries is lower than in South Asian populations. The median intake of total vegetables, including pulses, among the controls in our study was 355 g/day, much higher than in the cohorts included in the pooled analysis (range: 77-226 g/day 32 ). Thus, the lower intake of vegetables and dietary fibre might have reduced the likelihood of finding associations in studies conducted among Western populations.…”
Section: Discussioncontrasting
confidence: 57%
“…Therefore, further studies are necessary to clarify the potential preventive effects of apples on lung cancer in smokers and never smokers. In contrast to lung cancer, the risk of colorectal and breast cancer resulted to Kubik (2008) (17) / female/non-smokers Wright (2008) (36) /female/never smokers Wright (2008) (36) /female/full cohort Linseisen (2007) (38) /female+male/never smokers Wright (2008) (36) /female/former smokers Linseisen (2007) (38) /female+male/full cohort Wright (2008) (36) /male/full cohort Wright (2008) (36) /male/former smokers Linseisen (2007) (38) /female+male/current smokers Smith-Warner (2003) (48) /female+male/full cohort Wright (2008) (36) /male/current smokers Wright (2008) (36) /male/never smokers Arts (2001) (43) /male/full cohort Feskanich (2000) (45) /female/full cohort Knekt (2002) (42) /male/full cohort Büchner (2010) (32) /female+male/full cohort Büchner (2010) (32) /female+male/current smokers Wright (2008) (36) /female/current smokers Linseisen (2007) (38) *The analysis was performed when two or more studies were available, †The risk estimates were calculated using the random-effect model. ‡Number of studies used to calculate the risk is indicated in parentheses.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies may be in part due to the low number of cohort studies, two for colonrectum (39,49) and three for breast (30,40,47) . It should be considered, however, that two pooled analyses were Theodoratou (2007) (20) Deneo-Pellegrini (1996) (28) Koushik (2007) (49) /male+female Lin (2006) (39) /male Lin (2006) (39) /female…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of 14 casecontrol studies and 3 cohort studies showed a reduced risk of breast cancer in relation to vegetable consumption, but with significant heterogeneity among studies, and only a weak, non-significant, association with fruit intake. 34 A subsequent pooled analysis of 9 cohort studies 35 found that neither fruit nor vegetable intake was significantly associated with breast cancer risk, suggesting that the associations observed in case-control studies may have been due to differential reporting of dietary intakes by cases and controls. The cohort studies were conducted in North America and Western Europe.…”
Section: Discussionmentioning
confidence: 99%